2003
DOI: 10.1084/jem.20021973
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D-mediated Natural Killer Cell Protection Against Cytomegalovirus Is Impaired by Viral gp40 Modulation of Retinoic Acid Early Inducible 1 Gene Molecules

Abstract: Natural killer (NK) cells play a critical role in the innate immune response against cytomegalovirus (CMV) infections. Although CMV encodes several gene products committed to evasion of adaptive immunity, viral modulation of NK cell activity is only beginning to be appreciated. A previous study demonstrated that the mouse CMV m152-encoded gp40 glycoprotein diminished expression of ligands for the activating NK cell receptor NKG2D on the surface of virus-infected cells. Here we have defined the precise ligands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
253
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(264 citation statements)
references
References 34 publications
11
253
0
Order By: Relevance
“…However, 11 other ORFs in MCMV were also shown to have MHC-like folds and to be transmembrane glycoproteins (26). Three of these, m145, m152, and m155 have subsequently been shown to sequester stress-induced molecules (MULT1, RAE1, and H60, respectively) that would normally engage the NKG2D-activating NK receptors and interfere with NK cell activation and virus control (27)(28)(29)(30). UL16 of HCMV is known to sequester only some of the human ligands for NKG2D: it does not affect MICA or ULBP3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 11 other ORFs in MCMV were also shown to have MHC-like folds and to be transmembrane glycoproteins (26). Three of these, m145, m152, and m155 have subsequently been shown to sequester stress-induced molecules (MULT1, RAE1, and H60, respectively) that would normally engage the NKG2D-activating NK receptors and interfere with NK cell activation and virus control (27)(28)(29)(30). UL16 of HCMV is known to sequester only some of the human ligands for NKG2D: it does not affect MICA or ULBP3.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent investigations have shown that three other ORFs which had been identified as having MHC-like folds in MCMV, m145 and m155, were able to mediate NK evasion, as these molecules sequestered cellular ligands that would bind the activating NK receptor NKG2D (27)(28)(29)(30).…”
Section: Low Passage and Clinical Isolates Of Hcmv Encode An Additionmentioning
confidence: 99%
“…Recent studies of CMV have focused on the selective modulation of NK cell-activating receptors by viral proteins (24,43). This is thought not only to impair NK cell-mediated lysis of infected cells, but also to delay NK cell activation of the adaptive response and subsequent polarization of the helper T cell response (44).…”
Section: Discussionmentioning
confidence: 99%
“…The large number of redundant inhibitors of MHC class I suggests an important role for CTLs in defending against herpesvirus infection. Similarly, many herpesviruses encode proteins that impair type I IFN induction or action (20)(21)(22)(23), and CMV has recently been found to encode proteins that block NK cellactivating receptors (24).…”
Section: Introductionmentioning
confidence: 99%
“…at the same concentration as that used for the innate and acute studies. Following a single injection of anti-NKG2D CX5 MAb, antibody can be detected up to 2 weeks postinjection, with reduced NKG2D receptor expression on NK cells lasting for at least 7 days (42,57,63,64, and L. L. Lanier, unpublished observations).…”
Section: Methodsmentioning
confidence: 99%